2017
DOI: 10.1523/jneurosci.2484-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Tumor Necrosis Factor-Alpha (TNF-α) Modulates Amyloid Pathology by Regulating Blood-Derived Immune Cells and Glial Response in the Brain of AD/TNF Transgenic Mice

Abstract: Increasing evidence has suggested that systemic inflammation along with local brain inflammation can play a significant role in Alzheimer's disease (AD) pathogenesis. Identifying key molecules that regulate the crosstalk between the immune and the CNS can provide potential therapeutic targets. TNF-α is a proinflammatory cytokine implicated in the pathogenesis of systemic inflammatory and neurodegenerative diseases, such as rheumatoid arthritis (RA) and AD. Recent studies have reported that anti-TNF-α therapy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
58
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 67 publications
(36 reference statements)
10
58
1
Order By: Relevance
“…Interestingly, it has been shown that although peripheral human TNF could modulate Ab pathology by increasing the phagocytic activity of microglia, it contributes to neuronal damage and synaptic loss as well (Paouri et al, 2017a). In contrast to these results, it has also been shown that TNF inhibits phagocytosis of Ab by microglia (Koenigsknecht & Landreth, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it has been shown that although peripheral human TNF could modulate Ab pathology by increasing the phagocytic activity of microglia, it contributes to neuronal damage and synaptic loss as well (Paouri et al, 2017a). In contrast to these results, it has also been shown that TNF inhibits phagocytosis of Ab by microglia (Koenigsknecht & Landreth, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In early AD onset, microglia may contribute to clearance of Aβ by phagocytosis, but later they initiate deleterious cascades by releasing pro‐inflammatory cytokines, which contribute to neuronal damage (Agostinho et al , ; Yang et al , ; Wang et al , ). Interestingly, it has been shown that although peripheral human TNF could modulate Aβ pathology by increasing the phagocytic activity of microglia, it contributes to neuronal damage and synaptic loss as well (Paouri et al , ). In contrast to these results, it has also been shown that TNF inhibits phagocytosis of Aβ by microglia (Koenigsknecht & Landreth, ).…”
Section: Discussionmentioning
confidence: 99%
“…The rats were randomly distributed into four groups: the control, control+infliximab, hyperammonemic, and hyperammonemic+infliximab group. Infliximab is an anti-TNF-a antibody that does not cross the bloodbrain barrier [40], binds to peripheral TNF-a, and reduces peripheral inflammation in rats with MHE or hyperammonemia [9,10,22]. Infliximab (Remicade; Merck Sharp & Dohme, Spain) was dissolved in saline (0.9% sodium chloride) and administered by i.v.…”
Section: Effects Of Chronic Hyperammonemia and Peripheral Anti-tnf-a mentioning
confidence: 99%
“…High levels of systemic TNFα can cross the blood-brain barrier (BBB), stimulating the microglia to secrete more TNFα as well as other proinflammatory factors and thus creating persistent and self-generated neuroinflammation [15]. Metabolic diseases such as obesity, hypertension, dyslipidemia, diabetes, and insulin resistance are associated with chronic systemic inflammation and a higher risk of developing neurodegenerative diseases such as Alzheimer's disease and PD [17][18][19][20][21][22][23]. Due to the importance of peripheral inflammatory processes in PD development [24][25][26], it is relevant to investigate more thoroughly the mechanisms involved.…”
Section: Introductionmentioning
confidence: 99%